Peningkatan Pemahaman Konsep Pembelajaran IPA dengan Menggunakan Model Predict, Observer, Explain (Poe) Berbantuan Video Animasi Siswa Sekolah Dasar - Ulandari, Liska; Surya, Yenni Fitra; Kusuma, Yanti Yandri; Rizal, M. Syahrul; Fadhilaturrahmi, Fadhilaturrahmi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to improve the ability to understand concepts in class V UPT SD Negeri 007 Bangkinang. The background of this research is the low ability to understand science subject concepts in class V. This research is a class follow-up research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were 1 teacher and 22 students, while the object was to use the POE (Predict, Observer, Explain) learning model to improve the ability to understand concepts. The research instrument consisted of teacher activity observation sheets, student activity observation sheets, documentation sheets and learning test sheets during learning using the POE (Predict, Observer, Explain) learning model. While the data analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, at the second meeting of cycle I the ability to understand the concept. The results of this study show that by using the animated video-assisted POE model in class V UPT SDN 007 Bangkinang there has been an increase, namely in cycle I meeting I students who completed 10 people or 45.46% with an average of 69.00, then in cycle I meeting II students who complete 13 people or 60% with an average value of 72.00. In cycle II meeting I, 15 students completed or 68.19% with an average score of 79.63, cycle II meeting II students completed 20 people or 90.10% with an average score of 87.55. By using the POE (Predict, Observer, Explain) learning model, it can improve the ability to understand the concepts of class V UPT SD Negeri 007 Bangkinang students. Keywords: Ability to Understand Concepts, POE Model (Predict, Observer, Explain)